Analysis of Industrial-Sector Labor Force Absorption in West Java during the 2017-2021 Period - Humaira, Naila Aysa; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Industrialization occurs in a country where the industrial sector makes the largest contribution to the economy. The purpose of it is to improve the economy, accelerate development, and increase employment opportunities. With the growth of industrial sector, unemployment rate of West Java is still one of the highest in Indonesia and the labor absorption in this sector is not the highest. This study aims to analyse the influence of UMK, workforce, investment, GDRP in the industrial sector, and number of industries in labor absorption in the industrial sector of West Java Province in 2017-2021. This research using panel regression as its method. The result of the research shows that UMK, investment, and GDRP of industrial sector has positive and significant influence while workforce and GDRP of industrial sector has no effect for labor force in industrial sector. UMK, workforce, investment, GDRP of industrial sector, and number of industries has positive and significant influence for labor absorption in West Java in 2017-2021 simultaneously.